Positive electrode material and preparation method thereof, positive electrode plate and battery

During the preparation of single crystal positive electrode material, single crystals are formed by using the fusing action of boron-containing compounds, and the new interface is repaired by sodium-containing phosphate in the second heat treatment, and the new interface is solved in the crushing treatment of positive electrode material. The problem of electrochemical performance has been significantly improved.

CN119430306APending Publication Date: 2025-02-14JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566216.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Single-crystal positive electrode material produces a new interface during the crushing process, resulting in an increase in material activity and prone to side reactions with the electrolyte, affecting the electrochemical performance.

Method used

The first additive containing boron is added to the first heat treatment, and the melting effect is used to promote the formation of single crystals; the second additive containing sodium phosphate is added to the second heat treatment, so that part of the sodium is entered into the initial positive electrode material for the first heat treatment. The lattice supplements sodium, and at the same time forms a phosphate coating on the surface of the material to repair the new interface.

Benefits of technology

It effectively improves the electrochemical performance of the positive electrode material, reduces the residual alkali content, and improves the structural stability and cycling performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430306A_ABST
    Figure CN119430306A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a positive electrode material and a preparation method thereof, a positive electrode plate and a battery, and the preparation method of the positive electrode material comprises the following steps: S1, uniformly mixing a precursor, a sodium source and a first additive, carrying out first heat treatment, cooling, and crushing the obtained material to obtain an initial positive electrode material; the first additive comprises a boron-containing compound, the chemical formula of the precursor is NiaFebMncMd (OH) 2, the chemical formula of the initial positive electrode material is NaxNiaFebMncMdO2, M comprises at least one of Li, B, Mg, Al, K, Ca, Co, V, Cr, Cu, Zn, Zr, Nb, Sr, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu, 0 < = a < = 1, 0 < = b < = 1, 0 < = c < = 1, 0 < = d < = 1, a + b + c + d = 1 and 0.6 lt; x < = 1; and S2, uniformly mixing the initial positive electrode material with a second additive, performing second heat treatment, cooling, and sieving to obtain the positive electrode material with the phosphate coating layer, therefore, the electrochemical performance of the prepared positive electrode material can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. Background Art

[0002] Layered oxide materials have two-dimensional transmission channels, fast active ion transmission, and high compaction density, so layered oxide materials have been widely used in positive electrode materials of batteries. x TMO 2 (TM is a transition metal) has attracted extensive research due to its rich compositional diversity and tunable electrochemical properties. Sodium battery layered cathode materials, like lithium battery cathode materials, can be divided into polycrystalline and single crystal. Generally, polycrystalline materials exist in the form of micron-level agglomerates, and there are a large number of grain boundaries inside the agglomerates. During the battery charging and discharging process, due to the anisotropic lattice changes, polycrystalline materials are prone to grain boundary cracking, resulting in secondary particle breakage, which leads to rapid increase in side reactions, increased impedance, and rapid decrease in electrical performance. As a cathode material, single crystal material has the morphology of single crystal particles, which can reduce grain boundaries, reduce the occurrence of side reactions, and increase compaction density, thereby increasing energy density. Compared with polycrystalline materials, single crystal materials have higher structural stability and therefore better cycle performance.

[0003] However, the preparation process of single crystal positive electrode materials usually includes a crushing process, during which new interfaces are inevitably generated, resulting in higher material activity and easy side reactions with the electrolyte, thereby affecting the electrochemical properties of the positive electrode material. Summary of the invention

[0004] In view of this, the embodiments of the present application provide a positive electrode material and a preparation method thereof, a positive electrode plate and a battery to solve at least one problem existing in the background technology.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0006] S1: uniformly mixing the precursor, the sodium source and the first additive, performing a first heat treatment, and crushing the obtained material after cooling to obtain an initial positive electrode material;

[0007] The first additive includes a boron-containing compound, and the chemical formula of the precursor is Ni a Fe b Mn c M d (OH) 2 The chemical formula of the initial positive electrode material is Na x Ni a Fe bMn c M d O 2 , wherein M includes at least one of Li, B, Mg, Al, K, Ca, Co, V, Cr, Cu, Zn, Zr, Nb, Sr, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, a+b+c+d=1, 0.6 <x≤1;

[0008] S2: After uniformly mixing the initial positive electrode material and a second additive, performing a second heat treatment, wherein the second additive includes a sodium-containing phosphate, cooling and sieving, to obtain the positive electrode material having a phosphate coating layer.

[0009] In combination with the first aspect of the present application, in an optional implementation manner, the mixing in step S1 is performed under stirring conditions at a rotation speed of 700 r / min to 1500 r / min; preferably, the mixing time is 0.2 h to 1 h.

[0010] In conjunction with the first aspect of the present application, in an optional implementation, the crushing process in step S1 includes a first crushing process and a second crushing process;

[0011] Preferably, the first crushing process includes a mechanical crushing process;

[0012] Preferably, the second crushing process comprises a jet milling process.

[0013] In conjunction with the first aspect of the present application, in an optional embodiment, the first additive further includes a metal oxide;

[0014] Preferably, the metal oxide includes CuO, Al 2 O 3 、ZrO 2 、TiO 2 , Nb 2 O 5 , CaO, MgO, ZnO, Fe 3 O 4 、MnO 2 , CoO, Co 2 O, SrO, BaO, WO 3 ,La 2 O 3 、Lu 2 O 3 、Sm 2 O 3 More preferably, the metal oxide comprises Al 2 O 3、ZrO 2 、TiO 2 , at least one of CaO, MgO, and CoO;

[0015] Preferably, based on the weight of the precursor, the total content of the boron element and the metal element in the first additive is 1000ppm to 4000ppm.

[0016] In conjunction with the first aspect of the present application, in an optional implementation manner, step S1 satisfies at least one of the following features:

[0017] (1) The sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate, and sodium nitrate;

[0018] (2) The first additive includes B 2 O 3 and / or H 3 BO 3 ;

[0019] (3) 0.8<x≤1;

[0020] (4) The temperature of the first heat treatment is 880° C. to 980° C.;

[0021] (5) The holding time of the first heat treatment is 10 h to 18 h;

[0022] (6) The heating rate of the first heat treatment is 1°C / min to 5°C / min;

[0023] (7) The first heat treatment is performed in an air atmosphere, and the air flow rate is 20 L / min to 500 L / min.

[0024] In conjunction with the first aspect of the present application, in an optional implementation manner, step S2 satisfies at least one of the following features:

[0025] (1) The second additive includes Na 3 PO 4 、Na 2 HPO 4 、NaH 2 PO 4 At least one of;

[0026] (2) Based on the weight of the initial positive electrode material, the content of phosphorus in the second additive is 500 ppm to 4000 ppm, preferably 500 ppm to 2500 ppm;

[0027] (3) The temperature of the second heat treatment is 300° C. to 550° C.;

[0028] (4) The holding time of the second heat treatment is 15h to 28h;

[0029] (5) The heating rate of the second heat treatment is 1°C / min to 5°C / min;

[0030] (6) The second heat treatment is carried out in an air atmosphere, and the air flow rate is 40 L / min to 500 L / min;

[0031] (7) The temperature after cooling in the cooling step is 80°C to 120°C.

[0032] In combination with the first aspect of the present application, in an optional implementation manner, step S1 and / or step S2 is performed under the condition that the ambient humidity is less than or equal to 10%.

[0033] In a second aspect, an embodiment of the present application provides a positive electrode material, which is prepared using the method for preparing the positive electrode material described in any one of the first aspects.

[0034] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode material prepared by the preparation method described in any one of the preparation methods in the first aspect or comprising the positive electrode material described in the second aspect.

[0035] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode plate described in the third aspect.

[0036] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0037] The positive electrode material and preparation method thereof, positive electrode plate and battery provided in the embodiments of the present application are characterized by adding a first additive including a boron-containing compound in the first heat treatment and adding a second additive including a sodium-containing phosphate in the second heat treatment. In this way, the fluxing effect of the boron-containing compound is utilized, which is beneficial to the formation of single crystals during the first heat treatment on the one hand, and can allow part of the sodium in the second additive to enter the initial positive electrode material for lattice sodium replenishment during the second heat treatment on the other hand. At the same time, the second additive forms a phosphate coating layer on the surface of the initial positive electrode material to repair the new interface generated in the crushing process of the initial positive electrode material, thereby effectively improving the electrochemical performance of the finally obtained positive electrode material.

[0038] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0040] Figure 1 is a scanning electron microscope image of the positive electrode material obtained after the first heat treatment;

[0041] Figure 2 This is a scanning electron microscope image of the positive electrode material after airflow pulverization treatment;

[0042] Figure 3 A schematic flow chart of a method for preparing a positive electrode material provided in an embodiment of the present application. DETAILED DESCRIPTION

[0043] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.

[0044] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.

[0045] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0046] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.

[0047] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.

[0048] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.

[0049] The preparation process of single crystal positive electrode materials usually includes a first heat treatment (specifically, sintering) and a crushing treatment (specifically, air flow milling treatment). In the air flow milling treatment, high-speed airflow generated by compressed air is used to cause collisions between particles, thereby breaking up the agglomerated single crystal materials after sintering to achieve micronization. New interfaces are inevitably generated during the air flow milling process. Figure 1 This is a scanning electron microscope image of the positive electrode material obtained after the first heat treatment. Figure 2 This is a scanning electron microscope image of the positive electrode material after airflow pulverization. Figure 1 and Figure 2 It can be seen from the comparison that after the airflow crushing treatment, new interfaces appear in the positive electrode material (such as Figure 2 This will increase the activity of the material, making it easier for the positive electrode material to react with the electrolyte, thereby reducing the electrochemical performance of the positive electrode material.

[0050] In the related art, a coating layer is formed on the surface of the positive electrode material by a secondary sintering coating method, for example, an oxide coating method is used to improve the electrochemical performance of the positive electrode material. However, oxide coating will inevitably reduce the specific capacity of the material and affect the energy density of the battery.

[0051] Based on this, the present invention provides a method for preparing a positive electrode material. Figure 3 The method for preparing the positive electrode material provided in the embodiment of the present application comprises the following steps:

[0052] S1: After the precursor, the sodium source and the first additive are mixed evenly, a first heat treatment is performed, and after cooling, the obtained material is crushed to obtain an initial positive electrode material; the first additive includes a boron-containing compound, and the chemical formula of the precursor is Ni a Fe b Mn c M d (OH) 2 , the chemical formula of the initial cathode material is Na x Ni a Fe b Mn c M d O 2, wherein M includes at least one of Li, B, Mg, Al, K, Ca, Co, V, Cr, Cu, Zn, Zr, Nb, Sr, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, a+b+c+d=1, 0.6 <x≤1;

[0053] S2: After uniformly mixing the initial positive electrode material and the second additive, performing a second heat treatment, wherein the second additive includes a sodium-containing phosphate, the mixture is cooled and sieved to obtain a positive electrode material having a phosphate coating layer.

[0054] In an embodiment of the present application, a first additive including a boron-containing compound is added in the first heat treatment, and a second additive including a sodium-containing phosphate is added in the second heat treatment. In this way, the fluxing effect of the boron-containing compound is utilized, which is beneficial to the formation of single crystals during the first heat treatment on the one hand, and on the other hand, during the second heat treatment, part of the sodium in the second additive can enter the initial positive electrode material for lattice sodium replenishment. At the same time, the second additive forms a phosphate coating on the surface of the initial positive electrode material to repair the new interface generated by the initial positive electrode material during the crushing process, that is, part of the sodium ions are accelerated to diffuse in the solid phase to the new interface of the material crushing under the fluxing effect of the boron-containing compound, and lattice sodium replenishment (also called lattice sodium embedding) is performed while completing the repair of the new interface, thereby effectively improving the electrochemical properties of the final positive electrode material.

[0055] In some embodiments, the mixing of the precursor, the sodium source and the first additive in step S1 can be carried out under stirring conditions at a speed of 700 r / min to 1500 r / min, so that the precursor, the sodium source and the first additive can be mixed more fully and evenly, thereby facilitating the preparation of a high-quality initial positive electrode material through the first heat treatment. Specifically, for example, the precursor, the sodium source and the first additive can be placed in a mixer for full mixing, and the type of the mixer is not specifically limited here.

[0056] Furthermore, the mixing time of the precursor, the sodium source and the first additive can be 0.2h to 1h, which can further ensure the uniformity and sufficiency of the mixing of the precursor, the sodium source and the first additive, thereby further improving the quality of the initial positive electrode material obtained.

[0057] The "sodium source" in step S1 refers to a compound for providing sodium. Exemplarily, the sodium source may include at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate, and sodium nitrate. It should be noted that in actual preparation, the amount of sodium source added may be 1%-3% in excess of the amount of the sodium source material to compensate for the loss caused by sodium volatilization during the first heat treatment process.

[0058] The first additive in step S1 may include B 2 O 3 and / or H 3 BO 3 . B 2 O 3 and / or H 3 BO 3 It has a good fluxing effect, can better promote the formation of single crystals in the first heat treatment process, and can better promote part of the sodium in the second additive to enter the initial positive electrode material for lattice sodium replenishment in the subsequent second heat treatment process, thereby better improving the electrochemical properties of the prepared positive electrode material.

[0059] In some embodiments, the first additive in step S1 may further include metal oxides. The metal oxides can be doped into the initial positive electrode material during the first heat treatment process to stabilize the material structure and thereby improve the cycle performance of the positive electrode material.

[0060] For example, the metal oxide may include CuO, Al 2 O 3 、ZrO 2 、TiO 2 , Nb 2 O 5 , CaO, MgO, ZnO, Fe 3 O 4 、MnO 2 , CoO, Co 2 O, SrO, BaO, WO 3 ,La 2 O 3 、Lu 2 O 3 、Sm 2 O 3 Further, the metal oxide may include Al 2 O 3 、ZrO 2 、TiO 2 , CaO, MgO, and CoO. These metal oxides can better stabilize the structure of the positive electrode material, thereby further improving the cycle performance of the positive electrode material.

[0061] It can be understood that when the amount of the first additive added is small, the effect of improving the performance of the positive electrode material is not significant enough. When the amount of the first additive added is large, too much additive cannot be effectively doped into the positive electrode material, which will cause material waste, and the residual dopant may affect the performance of the final positive electrode material. Therefore, in some specific embodiments, based on the weight of the precursor, the total content of boron and metal elements in the first additive can be 1000ppm to 4000ppm, for example, 1000ppm, 2000ppm, 3000ppm, 4000ppm or any value between any two of the above numerical ranges.

[0062] The step of the first heat treatment in step S1 may be: placing the mixed precursor, sodium source and first additive in a box furnace, and performing the first heat treatment under an air atmosphere. In this way, the water vapor and carbon dioxide generated in the first heat treatment can be taken away by the flow of gas, the residual alkali on the surface of the material can be reduced, and the treatment effect of the first heat treatment can be improved. Specifically, the air flow rate can be 20L / min to 500L / min, wherein the air can be, for example, dry compressed air, so that the water vapor and carbon dioxide generated in the first heat treatment can be better taken away. In some other embodiments of the present application, the situation of performing the first heat treatment under an inert atmosphere is not excluded.

[0063] In actual preparation, air can be introduced into the bottom and side of the box-type furnace, wherein the air flow rate at the bottom of the box-type furnace can be 300L / min to 500L / min; the air flow rate at the side of the box-type furnace can be 20L / min to 80L / min. This can further improve the fluidity of the gas, thereby further reducing the residual alkali on the surface of the material and further improving the treatment effect of the first heat treatment.

[0064] When the temperature of the first heat treatment is low, it is not conducive to the formation of a high-quality single-crystalline positive electrode material. When the temperature of the first heat treatment is high, it may cause the structure of the single-crystalline positive electrode material to be destroyed, thereby affecting the performance of the material. Therefore, in some specific embodiments, the temperature of the first heat treatment can be 880°C to 980°C, for example, it can be 880°C, 900°C, 920°C, 940°C, 960°C, 980°C or any value between any two of the above numerical ranges.

[0065] The heating rate and holding time of the first heat treatment are also closely related to the effect of the first heat treatment. Therefore, in some specific embodiments, the heating rate of the first heat treatment can be 1°C / min to 5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between any two of the above numerical ranges. In this way, the material can be heated more evenly, that is, the temperature distribution inside the material is more uniform. The holding time of the first heat treatment can be 10h to 18h, for example, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h or any value between any two of the above numerical ranges. In this way, the quality of the initial positive electrode material formed can be further guaranteed, thereby improving the performance of the final positive electrode material.

[0066] The material obtained after the first heat treatment is usually a bulk material. Therefore, in some embodiments, the crushing process in step S1 may include a first crushing process and a second crushing process. Specifically, the first crushing process may include, for example, a mechanical crushing process; the second crushing process may include, for example, an air flow crushing process. Exemplarily, the bulk material may first be quickly crushed to a relatively small size by mechanical crushing, for example, the maximum particle size of the treated material may be controlled to be less than or equal to 2 mm; then the agglomerated material may be further separated by air flow crushing, and the particle size of the material may be further reduced after strong collision and friction of the high-speed airflow in the air flow crusher, for example, the median particle size of the treated material may be controlled to be 8 μm to 12 μm, so that an initial positive electrode material with a suitable particle size may be obtained, which is convenient for the subsequent preparation of a positive electrode material with a higher quality.

[0067] It should be noted that the above-mentioned crushing of materials by mechanical crushing and air flow crushing is only an example. The present application does not exclude the use of other crushing processes for crushing. Specifically, as to the type of crushing process and whether to use one or more crushing processes for crushing, technicians in this field can choose according to actual needs, as long as the particle size of the initial positive electrode material can be controlled within an appropriate range.

[0068] In the present embodiment, the chemical formula of the prepared initial positive electrode material is Na x Ni a Fe b Mn c M d O 2, where \(0\leq a\leq1\), \(0\leq b\leq1\), \(0\leq c\leq1\), \(0\leq d\leq1\), and \(a + b + c + d=1\); further, \(0\lt a\leq0.4\), \(0\lt b\leq0.4\), \(0\lt c\leq0.6\), \(0\lt d\leq0.4\), and \(a + b + c + d = 1\). In the chemical formula of the above-mentioned initial cathode material, \(0.6\lt x\leq1\). When \(0.6\lt x\leq0.8\), the initial cathode material includes a layered oxide with a P2-phase structure. In some specific embodiments, \(0.8\lt x\leq1\), so that the initial cathode material includes a layered oxide with an O3-phase structure, and the proportion of sodium in the material is relatively high, thereby further improving the specific capacity of the material.

[0069] In some embodiments, the mixing of the initial cathode material and the second additive in step S2 can be carried out under stirring conditions at a rotation speed of 300 r / min to 800 r / min, so that the initial cathode material and the second additive can be mixed more fully and evenly, which is beneficial to better sodium lattice compensation for the initial cathode material through the second heat treatment and forming a phosphate coating layer with higher quality on the surface of the initial cathode material. Specifically, for example, the initial cathode material and the second additive can be placed in a mixer for full mixing, and the type of the mixer is not specifically limited here.

[0070] Further, the mixing time of the initial cathode material and the second additive can be 0.2 h to 1 h, so as to further ensure the uniformity and sufficiency of the mixing of the initial cathode material and the second additive, thereby further improving the performance of the prepared cathode material.

[0071] In some embodiments, the second additive in step S2 may include at least one of Na 3 PO 4 , Na 2 HPO 4 , and NaH 2 PO 4 .

[0072] Due to the addition of the first additive including a boron-containing compound in the above-mentioned first heat treatment process, in the second heat treatment process, under the fluxing action of the boron-containing compound, some sodium ions in the sodium-containing phosphate accelerate solid-phase diffusion into the initial cathode material for lattice sodium compensation. At the same time, the sodium-containing phosphate can form a phosphate coating layer on the surface of the initial cathode material, thereby repairing the new interface generated during the crushing treatment of the initial cathode material, and thus achieving the effect of improving the electrochemical performance of the finally prepared cathode material.

[0073] Specifically, taking the second additive including sodium dihydrogen phosphate as an example, during the second heat treatment process, when sodium dihydrogen phosphate is heated to above a certain temperature, such as 250°C, sodium dihydrogen phosphate will lose all of its crystalline water and be converted into a white powder anhydrous form of sodium pyrophosphate, which is coated on the surface of the initial positive electrode material.

[0074] In the second heat treatment, when the amount of the second additive is low, that is, the amount of the sodium-containing phosphate is low, it will affect the effect of the lattice sodium supplementation of the initial positive electrode material, and it is not conducive to the formation of a phosphate coating layer of good quality on the surface of the initial positive electrode material. When the amount of the second additive is high, that is, the amount of the sodium-containing phosphate is high, it may cause the residual alkali on the surface of the material to increase, thereby affecting the performance of the positive electrode material. Therefore, in some specific embodiments, based on the mass of the initial positive electrode material, the content of phosphorus in the second additive can be 500ppm to 4000ppm, for example, 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm or any value between any two of the above numerical ranges. In this way, the effect of lattice sodium supplementation and coating of the initial positive electrode material can be guaranteed, the residual alkali on the surface of the material can be reduced, the processing performance of the material can be improved, and the electrochemical performance of the final positive electrode material can be improved.

[0075] Furthermore, based on the mass of the initial positive electrode material, the content of phosphorus in the second additive may be 500 ppm to 2500 ppm, so as to better improve the electrochemical performance of the final positive electrode material.

[0076] The second heat treatment step in step S2 may be: placing the mixed initial positive electrode material and the second additive in a box furnace, and performing a second heat treatment under an air atmosphere. In this way, the water vapor and carbon dioxide generated in the second heat treatment can be taken away by the flow of gas, the residual alkali on the surface of the material can be reduced, and the treatment effect of the second heat treatment can be improved. Specifically, the air flow rate can be 40L / min to 500L / min, wherein the air can be, for example, dry compressed air, so that the water vapor and carbon dioxide generated in the second heat treatment can be better taken away. In some other embodiments of the present application, the second heat treatment under an inert atmosphere is not excluded.

[0077] In actual preparation, air can be introduced into the bottom and side of the box-type furnace, wherein the air flow rate at the bottom of the box-type furnace can be 300L / min to 500L / min; the air flow rate at the side of the box-type furnace can be 40L / min to 100L / min. This can further improve the fluidity of the gas, thereby further reducing the residual alkali on the surface of the material.

[0078] When the temperature of the second heat treatment is low, the ion diffusion process is relatively slow, which will affect the effect of lattice sodium supplementation and coating of the initial positive electrode material. When the temperature of the second heat treatment is high, the crystallinity of the material becomes high, which easily leads to material agglomeration. After the second heat treatment, the obtained positive electrode material must be crushed before screening, which not only increases the process cost, but also causes the loss of the coating effect of the original phosphate coating layer on the initial positive electrode material. Therefore, in some specific embodiments, the temperature of the second heat treatment can be 300°C to 550°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or any value between any two of the above numerical ranges.

[0079] When the holding time of the second heat treatment is short, it is not conducive to the diffusion of sodium ions into the initial positive electrode material for lattice sodium supplementation, nor is it conducive to the formation of a complete high-quality phosphate coating layer on the surface of the initial positive electrode material. When the holding time of the second heat treatment is long, the crystallinity of the material will increase due to the long time of ion solid phase diffusion, which will lead to material agglomeration. After the second heat treatment, the obtained positive electrode material must be crushed before it can be sieved, which will not only increase the process cost, but also cause the original phosphate coating layer to lose the coating effect of the initial positive electrode material. Therefore, in some specific embodiments, the holding time of the second heat treatment is 15h to 28h, for example, it can be 15h, 17h, 20h, 22h, 24h, 26h, 28h or any value between any two of the above numerical ranges. In this way, by appropriately extending the time of the second heat treatment, even at a relatively low second heat treatment temperature, under the fluxing effect of the boron-containing compound in the first additive, it can be ensured that the sodium ions in the second additive can be better embedded in the crystal lattice for sodium replenishment, and better complete the repair of the new interface generated by the initial positive electrode material during the crushing process.

[0080] In some specific embodiments, the heating rate of the second heat treatment can be 1°C / min to 5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between any two of the above ranges. In this way, the material can be heated more evenly, that is, the temperature distribution inside the material is more even, thereby improving the effect of the second heat treatment.

[0081] In some specific embodiments, the temperature after cooling in the cooling step in step S2 can be 80°C to 120°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C or any value between any two of the above ranges. That is, after the second heat treatment is completed, when the temperature is about to reach 80°C to 120°C, the positive electrode material is taken out, so that even when the humidity of the actual preparation environment is high, the side reaction between the prepared positive electrode material and the moisture in the air can be better avoided, thereby better ensuring the performance of the positive electrode material.

[0082] In some specific embodiments, the above step S1 and / or step S2 can be performed under the condition that the ambient humidity is less than or equal to 10%. Specifically, all the steps in the above step S1, or all the steps in the above step S2, or all the steps in the above steps S1 and S2 can be performed under the condition that the ambient humidity is less than or equal to 10%, so that the side reaction between the material and the moisture in the air can be better avoided, thereby better ensuring the performance of the final positive electrode material. Further, the above step S1 and / or step S2 can be performed under the condition that the ambient humidity is less than or equal to 5%.

[0083] It can be understood that when the ambient humidity is less than or equal to 10%, there is basically no need to consider the problem of side reactions between water vapor in the environment and the material. Therefore, when step S2 is performed under the condition that the ambient humidity is less than or equal to 10%, the temperature after cooling in the cooling step of the above-mentioned step S2 can also be room temperature.

[0084] The embodiment of the present application also provides a positive electrode material, which is prepared by the preparation method of the positive electrode material described in any of the above embodiments.

[0085] An embodiment of the present application also provides a positive electrode plate, including a positive electrode material prepared by the method for preparing the positive electrode material described in any of the above embodiments or including the positive electrode material described in the above embodiments.

[0086] It should be understood that the beneficial effects of the positive electrode material prepared by the method for preparing the positive electrode material described in any of the above embodiments are all applicable to the positive electrode plate.

[0087] An embodiment of the present application also provides a battery, comprising the positive electrode plate described in the above embodiment.

[0088] It should be understood that the beneficial effects of the above-mentioned positive electrode plate are all applicable to the battery. Therefore, the electrochemical performance of the battery in the embodiment of the present application is good.

[0089] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples.

[0090] Example 1

[0091] The preparation of the positive electrode material in this embodiment includes the following steps:

[0092] S101: First, Ni 0.30 Fe 0.33 Mn 0.33 Zn 0.04 (OH) 2 (precursor) and sodium carbonate were placed in a high-speed mixer at a molar ratio of 1:0.51, and then Ni 0.30 Fe 0.33 Mn 0.33 Zn 0.04 (OH) 2 Based on the mass of 2 O 3 and ZrO with Zr content of 1000ppm 2 Next, the materials were mixed in a high-speed mixer at a speed of 1000 rpm / min for 0.5 h to obtain a uniformly mixed powder. Then, the mixed powder was placed in an atmosphere box furnace with a bottom air flow rate of 350 L / min and a side air flow rate of 40 L / min, and the temperature was increased to 960° C. at a heating rate of 3° C. / min and then sintered for 16 h (first heat treatment). After natural cooling, the first sintered material was obtained;

[0093] S102: The first sintered material obtained in step S101 is placed in a crusher, and after the particle size is crushed to less than 2 mm, it is placed in a jet mill and crushed to a median particle size D50 of about 9 μm, thus obtaining a layered oxide single crystal material NaNi 0.30 Fe 0.33 Mn 0.33 Zn 0.04 O 2 (initial cathode material);

[0094] S103: First, the layered oxide single crystal material NaNi obtained in step S102 0.30 Fe 0.33 Mn 0.33 Zn 0.04 O 2 With P content of 1500ppm (NaNi 0.30 Fe 0.33 Mn 0.33 Zn 0.04 O 2 The weight of Na 2 HPO 4Place it in a high-speed mixer and mix it at a speed of 600 rpm / min for 0.5h. Then, place the evenly mixed powder in an atmosphere box furnace with a bottom air flow rate of 350L / min and a side air flow rate of 40L / min. Heat it to 450°C at a heating rate of 3°C / min and sinter it for 20h (second heat treatment). When the furnace temperature drops to 80°C, take out the material, cool it and sieve it to obtain a layered oxide single crystal material after interface repair (positive electrode material with a phosphate coating layer).

[0095] Example 2

[0096] The preparation of the positive electrode material in this embodiment is basically the same as that in Embodiment 1, except that: in step S103, NaNi 0.30 Fe 0.33 Mn 0.33 Zn 0.04 O 2 Based on the weight of 2 HPO 4 .

[0097] Example 3

[0098] The preparation of the positive electrode material in this embodiment is basically the same as that in Embodiment 1, except that: in step S103, NaNi 0.30 Fe 0.33 Mn 0.33 Zn 0.04 O 2 Based on the weight of 2 HPO 4 .

[0099] Example 4

[0100] The preparation of the positive electrode material in this embodiment is basically the same as that in embodiment 1, except that: the precursor in step S101 is Ni 0.25 Cu 0.08 Fe 0.33 Mn 0.33 (OH) 2 .

[0101] Example 5

[0102] The preparation of the positive electrode material in this embodiment is basically the same as that in embodiment 1, except that: the precursor in step S101 is Ni 0.25 Ti 0.02 Zn 0.02 Fe 0.33 Mn 0.33 (OH) 2 .

[0103] Example 6

[0104] The preparation of the positive electrode material in this comparative example is basically the same as that in Example 1, except that: in step S103, NaNi 0.30 Fe 0.33 Mn 0.33 Zn 0.04 O 2 Based on the weight of 2 HPO 4 .

[0105] Comparative Example 1

[0106] The preparation of the positive electrode material in this comparative example is different from that in Example 1 in that it only includes step S101 and step S102 in Example 1, but does not include step S103 in Example 1.

[0107] Comparative Example 2

[0108] The preparation of the positive electrode material in this comparative example is basically the same as that in Example 1, except that: Na is not added in step S103 2 HPO 4 .

[0109] Comparative Example 3

[0110] The preparation of the positive electrode material in this comparative example is basically the same as that in Example 1, except that: B is not added in step S101 2 O 3 .

[0111] The positive electrode materials obtained in the above-mentioned embodiments and comparative examples were subjected to residual alkali test and electrochemical performance test.

[0112] (1) Residual alkali test: The positive electrode material samples are dissolved and extracted with ultrapure water and ethanol respectively, and the alkaline substances in the positive electrode material samples are titrated with hydrochloric acid standard titration solution. The potentiometer indicates the titration end point. The residual alkali content of the positive electrode material is calculated using sodium hydroxide, sodium carbonate and sodium bicarbonate. Specifically, the specified tester indicator electrode, stirrer, and burette are immersed in the solution, the positive electrode material is dissolved in ultrapure water or ethanol, and titrated with a calibrated hydrochloric acid standard solution. The reaction equation is: H + +OH - =H 2 O,H + +CO 3 2- =HCO 3 - +H 2 O,H + +HCO 3 - =H 2O+CO 2 The residual alkali value of the positive electrode material was calculated by calculating the volume (mL) of the hydrochloric acid standard solution consumed in each stage. The test results are shown in Table 1.

[0113] (2) The positive electrode materials obtained in the above embodiments and comparative examples were made into batteries and their electrochemical performance was tested.

[0114] The preparation of the battery includes the following steps: first, the positive electrode material, conductive carbon black (super-P) and polyvinylidene fluoride (PVDF) are ground and mixed evenly according to a mass ratio of 9:0.5:0.5, and then N-methylpyrrolidone (NMP) is added to prepare a positive electrode slurry, and then the positive electrode slurry is evenly coated on the pretreated aluminum foil, and placed in a blast drying oven at 80°C for 1 hour, and then placed in a vacuum drying oven at 120°C for 12 hours, and then cut into a circle with a diameter of 14 mm as a positive electrode sheet using a cutting machine, a sodium metal sheet with a diameter of 14 mm and a thickness of 0.2 mm is used as a negative electrode, a 0.1 mol / L mixed solution of sodium perchlorate, ethylene carbonate and dimethyl carbonate is used as an electrolyte, and a glass fiber with a diameter of 16 mm is used as a diaphragm, and a CR2032 button battery is assembled in a glove box filled with high-purity argon.

[0115] The performance test of the battery is as follows: set the discharge cut-off voltage to 2.0V, the charge cut-off voltage to 4.0V, and use the constant current charge and discharge mode.

[0116] The specific test method for the 0.1C first-cycle discharge capacity is: constant current charging to 4.0V at a current density of 0.1C; constant current discharge to 2.0V at a current density of 0.1C, and the discharge capacity at this time is recorded as the 0.1C first-cycle discharge capacity.

[0117] The specific test method of 1C discharge capacity is: constant current charging to 4.0V at a current density of 1C; constant current discharge to 2.0V at a current density of 1C, and the discharge capacity at this time is recorded as the 1C discharge capacity.

[0118] The specific test method for the capacity retention rate of 1C cycle for 200 cycles: charge at constant current to 4.0V at a current density of 1C; discharge at constant current to 2.0V at a current density of 1C, and record the discharge capacity at this time as the first cycle 1C discharge capacity; repeat the above charge and discharge steps 200 times, and record the 200th cycle 1C discharge capacity; The capacity retention rate of 1C cycle for 200 cycles = (200th cycle 1C discharge capacity / first cycle 1C discharge capacity) * 100%.

[0119] The test results of the 0.1C first cycle discharge capacity, 1C discharge capacity and capacity retention rate of the positive electrode material after 200 cycles at 1C in the battery are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] It can be seen from the data in Table 1 that the residual alkali content of the positive electrode materials prepared in Examples 1 to 6 is significantly lower than that in Comparative Examples 1 to 3. The batteries prepared from the positive electrode materials prepared in Examples 1 to 6 have increased discharge capacity relative to the batteries prepared from the positive electrode materials prepared in Comparative Examples 1 to 3, and the capacity retention rate after 200 cycles at 1C is significantly increased. It can be seen that in the present application, by adding a first additive including a boron-containing compound in the first heat treatment and adding a second additive including a sodium-containing phosphate in the second heat treatment, the fluxing effect of the boron-containing compound is utilized, which is beneficial to the formation of single crystals during the first heat treatment on the one hand, and on the other hand, during the second heat treatment, part of the sodium in the second additive can enter the initial positive electrode material for lattice sodium replenishment. At the same time, the second additive forms a phosphate coating on the surface of the initial positive electrode material to repair the new interface generated by the initial positive electrode material during the crushing process, that is, part of the sodium ions accelerate the solid phase diffusion to the new interface of the material crushing under the fluxing effect of the boron-containing compound, and complete the repair of the new interface while performing lattice sodium replenishment. This can not only reduce the residual alkali on the surface of the positive electrode material, but also enable the positive electrode material to have a higher gram capacity and good cycle stability, thereby effectively improving the electrochemical performance of the battery.

[0124] In addition, it can be seen from the data of Examples 1 to 3 and Example 6 that in Example 6, NaNi 0.30 Fe 0.33 Mn 0.33 Zn 0.04 O 2 Based on the weight of 2 HPO 4 Due to the addition of a higher content of sodium phosphate, the residual alkali content of the positive electrode material is slightly higher, which in turn affects the capacity and cycle stability of the positive electrode material. Therefore, based on the mass of the initial positive electrode material, the phosphorus content in the second additive is 500ppm to 2500ppm, which is a more preferred solution.

[0125] In Comparative Example 1, the initial positive electrode material was not subjected to a second heat treatment, i.e., no second additive including sodium-containing phosphate was added for secondary sintering. Therefore, the initial positive electrode material could not be lattice-replenished with sodium and the new interface generated by the initial positive electrode material during the crushing process could not be repaired, resulting in a high residual alkali content in the material obtained in the comparative example, and the material's capacity performance and cycle stability performance were both poor. Although the second heat treatment was performed in Comparative Example 2, i.e., secondary sintering was performed, so that the cycle performance was slightly improved relative to Comparative Example 1, since the second additive including sodium-containing phosphate was not added in the secondary sintering for lattice sodium replenishment and interface repair, the capacity performance and cycle stability performance of the material obtained in the comparative example were still poor relative to Example 1. In Comparative Example 3, the first additive including the boron-containing compound is not added in the first heat treatment, that is, the fluxing effect of the flux is lacking in the second heat treatment, and the initial positive electrode material cannot be effectively lattice-filled with sodium and the new interface generated in the crushing process of the initial positive electrode material cannot be repaired. Therefore, the residual alkali content of the material obtained in this comparative example is high, and the capacity performance and cycle stability of the material are not good, which shows that the interface repair effect of the material without adding the flux in the first heat treatment is poor. In the present application, based on the new interface problem caused by the crushing of the material in the airflow crushing process during the preparation process of sodium-electrolyte layered oxide single crystal materials, a first additive including a boron-containing compound is added in the first heat treatment, and a second additive including a sodium-containing phosphate is added in the second heat treatment. While repairing the new interface, sodium is supplemented between the lattices, thereby effectively improving the gram capacity performance and cycle performance of the positive electrode material on the basis of improving the structural stability of the positive electrode material.

[0126] It should be noted that the positive electrode material embodiments, positive electrode material preparation method embodiments, positive electrode plate embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in the embodiments can be arbitrarily combined without conflict.

[0127] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A method for preparing a positive electrode material, characterized in that: The following steps are involved: S1: uniformly mixing the precursor, the sodium source and the first additive, performing a first heat treatment, and crushing the obtained material after cooling to obtain an initial positive electrode material; The first additive includes a boron-containing compound, and the chemical formula of the precursor is Ni a Fe b Mn c M d (OH)2, the chemical formula of the initial positive electrode material is Na x Ni a Fe b Mn c M d O2, wherein M includes at least one of Li, B, Mg, Al, K, Ca, Co, V, Cr, Cu, Zn, Zr, Nb, Sr, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, a+b+c+d=1, 0.6 <x≤1; S2: After uniformly mixing the initial positive electrode material and a second additive, performing a second heat treatment, wherein the second additive includes a sodium-containing phosphate, cooling and sieving, to obtain the positive electrode material having a phosphate coating layer.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: The mixing in step S1 is carried out under stirring conditions at a rotation speed of 700 r / min to 1500 r / min; preferably, the mixing time is 0.2 h to 1 h.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: The crushing process in step S1 includes a first crushing process and a second crushing process; Preferably, the first crushing process includes a mechanical crushing process; Preferably, the second crushing process comprises a jet milling process.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: The first additive also includes a metal oxide; Preferably, the metal oxide includes at least one of CuO, Al2O3, ZrO2, TiO2, Nb2O5, CaO, MgO, ZnO, Fe3O4, MnO2, CoO, Co2O, SrO, BaO, WO3, La2O3, Lu2O3, and Sm2O3; More preferably, the metal oxide includes at least one of Al2O3, ZrO2, TiO2, CaO, MgO, and CoO; Preferably, based on the weight of the precursor, the total content of the boron element and the metal element in the first additive is 1000ppm to 4000ppm.

5. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: Step S1 satisfies at least one of the following characteristics: (1) The sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate, and sodium nitrate; (2) The first additive includes B2O3 and / or H3BO3; (3)0.8<x≤1; (4) The temperature of the first heat treatment is 880° C. to 980° C.; (5) The holding time of the first heat treatment is 10 h to 18 h; (6) The heating rate of the first heat treatment is 1°C / min to 5°C / min; (7) The first heat treatment is performed in an air atmosphere, and the air flow rate is 20 L / min to 500 L / min.

6. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: Step S2 satisfies at least one of the following characteristics: (1) The second additive includes at least one of Na3PO4, Na2HPO4, and NaH2PO4; (2) Based on the weight of the initial positive electrode material, the content of phosphorus in the second additive is 500 ppm to 4000 ppm, preferably 500 ppm to 2500 ppm; (3) The temperature of the second heat treatment is 300° C. to 550° C.; (4) The holding time of the second heat treatment is 15h to 28h; (5) The heating rate of the second heat treatment is 1°C / min to 5°C / min; (6) The second heat treatment is carried out in an air atmosphere, and the air flow rate is 40 L / min to 500 L / min; (7) The temperature after cooling in the cooling step is 80°C to 120°C.

7. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: Step S1 and / or step S2 are performed under the condition that the ambient humidity is less than or equal to 10%.

8. A positive electrode material, characterized in that The cathode material is prepared by the method for preparing the cathode material according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material prepared by the preparation method according to any one of claims 1 to 7 or the positive electrode material according to claim 8.

10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.